The parental investment effect on immigrant children at schools: Employment and specialization of parents as an explaining variable for tasks achievement in second language - Figueiredo, Sandra (2018)
The present research study examines how family environment has an impact on immigrant children’s task performance considering the Socioeconomic Status (SES) of parents, but focusing two dimensions of the immigrant SES specificities (APA, 2012): the professional situation and related educational background (employment and specialization professions/work of parents). Economically disadvantaged families (parents unemployed or whose job is unspecialized) may be a predictor of different performances in a second language (L2), involving deficits for parental investment and for specific cognitive skills in childhood and adolescence. 108 learners of Portuguese as a L2, aged 8 to 17, from lower to middle socioeconomic backgrounds, completed four language and verbal reasoning tasks in European Portuguese: verbal analogies, semantic associations, picture identification and morphological extraction. A series of MANOVAs indicated that learners from lower socioeconomic backgrounds perform worse in the four administered tasks due to their parents' unemployment situation but students whose parents had unspecialized jobs performed better than those whose parents had specialized jobs. Unskilled jobs were confirmed as related to higher immigrant parental investment. Educational and cognitive implications will be discussed concerning how the participants differed in the tasks.